2005
DOI: 10.1007/s12126-005-1016-9
|View full text |Cite
|
Sign up to set email alerts
|

A psychosocial model of functional disability

Abstract: With advancing age, many older adults are vulnerable to a decline in physical functioning. Functional disability has been shown to affect the subjective well-being of the individual, and has been associated with increased morbidity and mortality. Social support is commonly assumed to protect people from the experience of psychological distress and enhance well-being. Other studies have demonstrated that satisfaction with social support, rather than the frequency with which support was received, is a powerful p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
0
9
1
Order By: Relevance
“…With regard to gender and ethnicity, we did not find differences in functional capacity. This stands in contrast to other reported studies linking these demographic characteristics to functional capacity (Fiksenbaum et al, 2005;Liang et al, 2003;Mendes de Leon et al, 2005). Previous studies, however, have been conducted with younger old adults and it is possible that gender and ethnicity differences converge at the very end of the biological lifespan.…”
Section: Functional Capacity 17contrasting
confidence: 81%
See 2 more Smart Citations
“…With regard to gender and ethnicity, we did not find differences in functional capacity. This stands in contrast to other reported studies linking these demographic characteristics to functional capacity (Fiksenbaum et al, 2005;Liang et al, 2003;Mendes de Leon et al, 2005). Previous studies, however, have been conducted with younger old adults and it is possible that gender and ethnicity differences converge at the very end of the biological lifespan.…”
Section: Functional Capacity 17contrasting
confidence: 81%
“…Such resources, however, are important when engaging in a number of daily activities. Other studies have also indicated a positive association between social support and functional capacity (Avlund et al, 2004;Fiksenbaum et al, 2005). Perhaps the continued encouragement by a social support system may prompt centenarians to continue their engagement in activities of daily living.…”
Section: Functional Capacity 17mentioning
confidence: 98%
See 1 more Smart Citation
“…These mechanisms increase the risk of depression (Holmes & Rahe, 1967). In addition, older adults live with functional disabilities and may become dependent, so that they react with feelings of hopelessness or worthlessness, which, in turn, increase their risk of depression (Fiksenbaum, Greenglass, Marques, & Eaton, 2005). Thus, nurses or health care providers should consider both a decrease of functional ability in older adults and the older adults' coping strategies, particularly emotional-focused coping strategies, in developing nursing intervention programs to reduce depression.…”
Section: Functional Abilitymentioning
confidence: 99%
“…11 Healthy lifestyles can predict less psychological distress 12 and less functional disability. 11 Healthy lifestyles can predict less psychological distress 12 and less functional disability.…”
Section: Introductionmentioning
confidence: 99%